2018
DOI: 10.1177/0003319718768658
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Mean Platelet Volume and Neutrophil to Lymphocyte Ratio Predicts Long-Term Major Adverse Cardiovascular Events After Percutaneous Coronary Intervention

Abstract: We hypothesized that the combination of a high neutrophil to lymphocyte ratio (NLR) and mean platelet volume (MPV) would be a stronger predictor of future cardiovascular events after percutaneous coronary intervention (PCI). Both NLR and MPV were measured in 364 consecutive patients undergoing PCI. The primary end point was the incidence of major adverse cardiovascular events (MACEs), including cardiac death, nonfatal myocardial infarction, and stent thrombosis. The median values of NLR and MPV were 2.8 and 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…The current understanding of the pathogenesis of atherosclerosis is focused on the "inflammatory hypothesis of atherothrombosis" theory [1,2]. Inflammatory cells and inflammatory signaling pathways play complex roles in the process of atherosclerosis, including initiating repair after vascular injury and mediating plaque instability and rupture, finally leading to acute coronary events [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The current understanding of the pathogenesis of atherosclerosis is focused on the "inflammatory hypothesis of atherothrombosis" theory [1,2]. Inflammatory cells and inflammatory signaling pathways play complex roles in the process of atherosclerosis, including initiating repair after vascular injury and mediating plaque instability and rupture, finally leading to acute coronary events [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an analysis by Rief et al [17] lately pointed out a relation between decreasing mean platelet volume (MPV) and CLTI. Apart from that, several previous studies have already targeted platelet parameters and white blood cell count parameters, as well as combinations of them, in order to investigate their role as prognostic markers in patients with coronary artery disease (CAD) [18,19,20,21,22] and cerebrovascular disease [23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…10 The NLR is also influenced by dehydration, overhydration, diluted blood specimens, and in vitro blood specimen handling. 8 In conclusion, based on the work of Choi et al, 4 future work should evaluate the use of both MPV and NLR in clinical practice. Together, the NLR þ MPV may well turn out to be more useful predictors of vascular risk than either marker separately.…”
mentioning
confidence: 98%
“…Considerable research in the last few years revealed that the mean platelet volume (MPV) and neutrophil-lymphocyte ratio (NLR) may play a role in the development, progression, and complication of several human disorders like metabolic syndrome (MS), atrial fibrillation, coronary artery disease. [1][2][3] In this issue of the journal, Choi et al 4 showed that in a multivariate Cox proportional hazards model, the combination of high NLR þ high MPV was independently (P ¼ .026) associated with major adverse cardiovascular events (including cardiac death, nonfatal myocardial infarction, and stent thrombosis).…”
mentioning
confidence: 99%
See 1 more Smart Citation